PENGARUH LABEL DAN PACKAGING PADA PRODUK LABU SIAM MUSTOFA TERHADAP TINGKAT PENJUALAN - Elfrida Satria Ona; Dian Puspita Sari; Katharina Alexandria Dede; Ana Setia; Rina Asmaul; Yunus Karyanto (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
Chayote (Sechium edule) is a local food that has good nutritional value for the human body. Chayote has a fairly good fiber content, namely 1.7 grams per 100 grams. Minimal processing in the form of fresh cuts is an option that can be done to increase distribution reach, improve safety and quality, speed up and simplify processing, and reduce waste in the form of waste that can pollute the environment. Apart from that, chayote contains antioxidants which can help prevent cancer by warding off free radicals, such as vitamin C and flavonoids. Many substances found in chayote, such as saponins, flavonoids, proteins, vitamin A, thiamin, and many more, have therapeutic uses. The majority of Indonesian people are not interested in consuming or processing chayote, even though chayote has many medicinal properties. To increase selling prices and gain popularity among Indonesian people, the chayote trade must be innovated. One way to make this happen is to turn it into a Mustofa Chayote. This research uses questionnaires, interviews and observation as data collection methods. If you look at how to answer the questionnaire, it is divided into two types, namely open questionnaires and closed questionnaires. The results of this research are that the value of product design, labels and packaging influences consumer interest. Our products are not only seen from their delicious taste and good food color, but also from their external appearance, namely attractive labels and packaging which really influence consumers' interest in buying the product.. Keywords: Chayote, Product Quality